Risk Factors of Brain Metastasis and Prognosis in HER2-Positive Breast Cancer: A Single-Institution Retrospective Analysis from China - Cai, Shuang-Long; Wang, Zhi-Hong; Chen, Xiao-Geng; Han, Lei; Gong, Guo-Xian; Chen, Yan-Ping; Lin, Xiu-Quan; Ma, Tao; Chen, Hong-Dan (Frontiers in Oncology, 2022)
Background: Brain metastasis (BM）frequently occurs in HER2-positive breast cancer patients, but the risk factors of BM in this type of patients are still unknown. Our study is to assess the risk factors of BM and prognostic analysis in HER2-positive breast cancer patients. Methods Univariate analysis used T test, Chi-square test and Fisher’s exact test to find out the risk factors for BM, and multivariable analysis was done with stepwise logistic regression analysis. Prognostic data analysis were estimated by the Kaplan–Meier method. Results A total of 228 HER2-positive breast cancer patients were included of whom 214 patients were postoperative metastatic patients and 14 patients were de-novo stage IV patients. Through comparing the stratified variables between 51 postoperative metastatic patients with brain metastasis and 163 postoperative metastatic patients without brain metastasis,the multivariate analysis showed that age ≤40 years（OR 2.321，95 % CI 1.089 to 4.948), first metastatic site with lung metastasis （OR 2.168，95 % CI 1.099 to 4.274) were independent risk factors for brain metastasis in HER2-positive breast cancer patients. Prognostic data of all 65 HER2-positive breast cancer patients with BM showed that the time from the diagnosis of breast cancer(BC) to development of breast cancer brain metastasis(BCBM) was 36.3 months (95%CI: 30.0 to 42.1 months); The time from the diagnosis of first recurrence and metastasis stage to diagnosis of BCBM was 11.3 months (95%CI: 7.1 to 18.4 months). The time from the diagnosis of BCBM to our follow-up data was 24.1 months (95%CI: 13.9 to 37.5 months) ; Up to follow-up data，a total of 38 patients had died, and the time of these 38 patients from the diagnosis of BM to the death was 11.0 months (95%CI: 9.0 to 20.4 months). Conclusion The prognosis of Her2-positive breast cancer patients with BM were poor due to lacking few effective treatments for BM. Age ≤40 years and first metastatic site with lung metastasis were the independent risk factors for brain metastasis in Her2-positive breast cancer patients. Future researchs about pre-emptive medical interventions may help to improve the prognosis of these high risk to develop BM in Her2-positive breast cancer patients.